Risk assessment of industrial excess heat collaborations – Empirical data from new and ongoing installations. (15th September 2022) - Lygnerud, Kristina; Klugman, Sofia; Fransson, Nathalie; Nilsson, Johanna
Abstract: Excess heat could meet approximately 25% of the heat demand in the European building sector. However, the recovery of excess heat is low, which has been attributed to financial, technical and organisational barriers. There is limited information on the perceived risk exposure of excess heat recovery at different points in time, before undertaking the investment or after having undertaken the investment, and at locations with existing district heating networks or not (greenfield). This is unfortunate because experience can enable new collaborations. In this paper, we compare the perceived risk exposure of four greenfield and two ongoing industrial excess heat recovery collaborations. In doing so, we confirm previously identified barriers, such as difficulty to agree on the value of excess heat, the risk of a single heat source and lack of regulation. We also find that, with experience, changes to the excess heat-generating processes are increasingly important, whereas, greenfield sites find the lack of 'know-how' to be risky. However, the main conclusion from this paper is that the risks of industrial excess heat recovery collaborations appear to be over-emphasised. In fact, risk exposure of industrial activity can be reduced through industrial waste heat recovery as excess heat is characterized by limited price fluctuations and new environmental requirements from customers and authorities can be met proactively. Combining experience with a standardised excess heat recovery policy should significantly reduce the risk exposure of new collaborations. Highlights: Risks of industrial excess heat recovery collaborations are over-emphasised. Excess heat exploitation is imperative to Europe's energy transition. Experience and policy making can make excess heat recovery a standard solution.